Study of Application of Software Defined Network to Real Networks - Manoranjitham, T; Sai Vijaya Kumar, K; Varshith, B (International Journal of Engineering and Technology, 2018)
This paper presents the application of Software Defined Network to Real Networks. Software Defined Networking is an intriguing concept in the networking and communication industry which provides various uses, from productive network operations to reduced costs in the networking field. The SDN architecture provides the network administrators to implement new network services and easy management of the network .This operation is done by separating the data plane and control plane that makes decision .The data plane forwards packet and control plane manages traffic. Â In this paper we are studying the application of SDN to Real Networks such as SDN for Internet of Things, Artificial Intelligence, 5G Networks, Wireless Networks.